Tutt* a tavola! - Giufre, Stacy; Masterson, Melina (Open textbook library., 2021)
This new open educational resource is for Elementary Italian. Our goal is for this book to be comprehensive, user-friendly, inclusive, and cost-effective. Tutt* a tavola has two parts, one for each course, with six chapters in each. Generally speaking, each chapter addresses three to four grammatical topics and includes a vocabulary section related to a cultural theme. The vocabulary is also incorporated into the grammatical presentations and exercises. There is also a short reading in each chapter regarding different aspects of culture and language, to address those questions of diversity and inclusion that are often missing from the textbooks we have used in the past. To include more culture, we have also included multimedia: each chapter begins with a song that is used as a starting point for the inductive presentation of the chapter’s content, and ends with a video (a film clip, an interview, social media) that summarizes the ideas covered.